P65 Using simulation-based learning to provide an introduction to human factors. (3rd November 2019) - Nalwaya, Prateek; Oxenham, Gregory; McGeoch, Luke; Clery, Philippa; Sewart, Emma; Kamalanathan, Kajan
Abstract : Background: In 2016, a report by Health Education England advocated using simulation based-learning and placing a greater emphasis on human factors (HF) training to improve patient safety across the NHS. 1 HF have been incorporated into several post-graduate training programmes, in particular anaesthesia, where potential risk to patient safety is high. Our innovative, simulation-based, one-day course sought to expand this training to final year medical students. Summary of work: In this pilot, we organised two training days and a total of 33 students attended. The course began with a brief introductory lecture about HF concepts. Following this, six scenarios were simulated; these scenarios were based on real experiences that illustrated different aspects of HF. Both before and after the course, the students completed a modified version of a 14-part questionnaire developed by Reedy et al . 2 to evaluate learning outcomes in HF training. Summary of results: The response rate was 100%. With respect to questions developed by Reedy et al. 2, using an ordinal Likert scale, we found that students' greatest mean improvement in confidence (2.27) was in 'monitoring the 'big picture' during a clinical scenario' and the least improvement (1.24) was seen in 'involving colleagues in your decision making'. With respect to our own questions, the greatest mean improvement in confidence was seen in 'reporting a system error or critical incident' (2.42). Pre-teaching and post-teaching feedback was analysed using a paired t-test and showed a significant improvement in human factor(s) skills (p<0.000001). Qualitative feedback revealed that students appreciated opportunities to practice dealing with problems commonly encountered in foundation training, such as dealing with challenging colleagues and system errors. Negative feedback was largely directed at only being able to participate in one scenario. Discussion and conclusions: Simulation-based learning improved the confidence of our final year medical students in criteria relating to HF. Evaluating whether increased confidence leads to behavioural change is, however, fraught with difficulty. We plan to organise this training day for the next cohort of final year medical students, and in our future study design plan to include follow-up to assess if there has been an impact on their clinical practice. Recommendations: We believe that a major strength of our design was in having the faculty member who developed the simulation scenario - based on their own clinical experiences - also leading the 'debrief' for that session. This grounding in reality made the learning points, discussion and reflection authentic. References: Health Education England, The Commission on Education and Training for Patient Safety (2016). Improving Safety Through Education and Training. Available at: https://www.hee.nhs.uk/sites/default/files/documents/Improving%20safety%20through%20education%20and%20training.pdf [Accessed 21 Apr 2019] Reedy G.B., Lavelle M., Simpson T. and Anderson J.E., 2017. Development of the Human Factors Skills for Healthcare Instrument: a valid and reliable tool for assessing interprofessional learning across healthcare practice settings. BMJ Simulation and Technology Enhanced Learning, 3(4), pp.135–141.